4(3x + 7) = 7

1) You can't do anything until you get rid of the parentheses. Use distributive property to get rid of those.

**12x + 28 = 7**

2) Now do the order of operations backwards. The first thing (going backwards) is addition/subtraction. What do you have in *your problem*? You have addition. The opposite of addition is subtraction.

**12x + 28 = 7**

** -28 -28**

**12x = -21**

3. Now you have 12x = -21. What operation is being used in the equation? Multiplication is. The opposite of multiplication is division. Now divide both sides by 12.

**12x = -21**

**x = -1.75**

4(3x+7)=7.

To solve for x, multiply by 4 to each of the terms inside the bracket in the left side:4*3x=12x. 4*-7=-28. The right side is retained as it is:

12x+28=7.

Subtract 28 from both sides to retain the unknown term 12x on the left and the known term or the numbers on the right:

12x+28-28=7-28.

Now 28-28 on the left cancel out.On the right 7-28= -21:

12x=-21.

Divide both sides by 12. On the left **12x/12 becomes x**.On the right -21/12, which is reduced to **-7/4** in the lowest equivalent fraction form.

Therefore, **x=-7/4 .**

Convert 7/4 in decimal form and attach the minus line at last.

7/4=1+3/4 =1.75.

Therefore,**x=-1.75 is our solution.**

Tally:

Put the solution, x=-1.75 in the original equation and see whether the equation is satisfied, in the sense the value on the left becomes equal to the right.

Left side :4*[3(-1.75)+7]=4*3(-1.75)+4*7=4*-5.25+28=-21+28=7.

Right side:7

Both sides are equal in value after putting x=-1.75. So the solution is verified.

im not sure how your teacher asked you to solve the equations, but theres simple steps to follow to figure out for x;

- you want to get rid of the brackets, to do this multiply the numbers in brackets by 4
- rewrite the question, it should now be 12x + 28 =7
- now you want to isolate x, to do this subtract 28 from both sides of the equation
- rewrite the equation once again, it should now be 12x = -21
- now divide both sides of the equation by 12
- rewrite the equation one more time and you have your answer. x= -1.75
- dont forget to check your answer! :)

**4(3x+7)=7**

In order to solve this we need to remove the parenthesis and then isolate x to find the value of x.

**4(3x+7)=7 **(multiply 3x and 7 by 4 to remove the brackets)

12x+28=7

12x+28-28=7-28 (subtract 28 from both sides)

12x=-21

12x/12=-21/12 (divide both sides by 12)

**x=-1.75 or -21/12 Answer.**

4(3x+7)=7

First Multiply 4 by everything in the parentheses and you will get

4 X (3x) + 4 X (7) = 7

12x + 28 = 7

Now subtract 28 from both sides

(12x + 28) -28 = (7) -28 The 28 will be cancelled out on the left side.

12x = -21

Now divide -21 by 12

12(12x) = (-21)12

You should get

x = -1.75

4(3x+7) = 7

Distribute the 4 : 12x + 28 = 7

subtract the 28 : 12x = -21

divide the 12 : -21 / 12

x = -21/12 but it can be simplified

divide both sides by 3

X = -7/4 , -1.75 , or -1 3/4

4(3x+7)=7

12x+28=7 multiply by 4

12x= -21 subtract 28 from all sides

x= -21/12 divide both sides by 12

Since you are solving for x you need to separate the variable from the others. To do that you need to distribute the x first of all

4(3x+7)=7

12x+28=7 then move the numbers on one side and isolate the variable

12x=-21

Divide by 12

x=-21/12 = -1.75 ` <br> `

First divide 4 on both sides.

Next, minus 7 from both sides

7/4-7=-5.25

Then divide -5.25 by 3, to get-1.75.

Solve for x:

4(3x+7)=7

okay so in order to do this, we stick with the golden rule: to get the unkown variable on one side of the equal side (also do the same thing to both sides) and all the other number on the other side

in order to get X by itself, you have to first divide both sides by 4

so you have (3X+7)=7/4 = 1.75

then you subtract 7 from both sides

3X= 7/4 -7 = 1.75 - 7

then divide the entire thing by 3

x= (7/4 - 7)/3 = (1.75-7)/3= (-5.25)/3= -1.75

4(3x+7)=7

**x = -1.75**

4(3x+7)=7

Divide both sides by 4

3x + 7 = 7/4

subtract 7

3x = (7/4) - 7

divide by 3

((7/4) - 7)/3

= -1.75

4(3x+7)=7

* distribute the 4

- (4 * 3x)= 12x
- (4 * 7) = 28

12x + 28 = 7

- subtract 28 in both sides
- +28 -28 = 0
- 7 - 28 = -21

12x = -21

- Divide 12 to both sides to get the x alone
- (12x / 12 ) = x
- (-21/12) = -1.75

**x = -1.75**

4(3x+7)=7

you have to get rid of the parenthesis

distribute the 4 within the parentheis

12x+28=7

subtract 28 from both sides

12x+28=7

-28 -28

12x=-21

divide by 12

12x=-21

/12 /12

x=-1.75

**4(3x+7)=7 ======>multiply 4 by 3x , 7**

**12x + 28 = 7 ========> add -28 both side**

**12x + 28 -28 = 7-28**

**12x = -21 =======> divid both side by 12**

**x = -21/12 = 1.75**